Nine new records of brittle stars (Echinodermata: Ophiuroidea) from Indian waters. Issue 5 (3rd July 2021) - Parameswaran, Usha V.; Gopal, Aiswarya; Abdul Jaleel, K. U.; Saravanane, N.
ABSTRACT: This paper presents nine new records of brittle stars for the Indian waters, collected between 49 and 957 m depths in the Arabian Sea, Bay of Bengal and Andaman Sea. Of these, Ophiolepis cardioplax and Ophiopsammus aequalis are being reported for the first time from the Indian Ocean, while Astrothorax waitei, Amphiophiura insolita, Ophialcaea tuberculosa and Ophioplocus declinans are new records for the northern Indian Ocean. Three other species – Amphiura ( Amphiura ) dejectoides, Amphiura ( Amphiura ) uncinata and Ophiopeza spinosa are recorded from nearby areas but are being reported for the first time from the Indian waters. Indophioderma ganapatii, described from Agatti Island, Lakshadweep is synonymized with Ophiopeza spinosa . The nine species described in this paper include several that have not been adequately described in literature or have rarely been documented at all.